Accelerating Bianchi I Universe with Time Varying Deceleration Parameter in f(G) Gravity - Palaspagar, M. S.; Khade, P. P.; Patil, P. R. (Journal of Scientific Research, 2026)
The present research aims at investigating the LRS Bianchi type I dark energy cosmological model within the framework of f(G) gravity. To obtain solutions for the field equations, a parametrization of the deceleration parameter is employed. The approximate best-fit values of the model parameters are obtained using the least squares method, incorporating observational constraints from available datasets such as the Hubble dataset and the Pantheon dataset by applying the Root Mean Square Error (RMSE) formula. The related cosmological parameters are graphed against redshift, and the universe's accelerated expansion is subsequently examined. Various physical parameters, including pressure, energy density, and energy conditions, are also discussed.